Hands-on matrix algebra using R active and motivated learning with applications - Vinod, Hrishikesh D., author (Singapore ; Hackensack, N.J. World Scientific, 2011)
Teaches matrix algebra, allowing the student to learn the material by actually working with matrix objects in modern computer environment of R. This book provides a comprehensive overview of matrix theory without being bogged down in proofs or tedium.
Matrix defined, deeper understanding using software -- Elementary geomentary geometry and algebra using R -- Vector spaces -- Matrix basics and R software -- Decision applications, payoff matrix -- Determinant and singularity of a square matrix -- The norm, rank and trace of a matrix -- Matrix inverse and solution of linear equations -- Eigenvalues and eigenvectors -- Similar matrices, quadratic and Jordan canonical forms -- Hermitian, normal and positive define matrices -- Kronecker products and singular value decomposition -- Simultaneous reduction and vec stacking -- Vector and matrix differentiation -- Matrix results for statistics -- Generalized inverse and patterned matrices -- Numerical accuracy and QR decomposition.
Online version: Vinod, Hrishikesh D., 1939- Hands-on matrix algebra using R. Singapore ; Hackensack, N.J. : World Scientific, ©2011 (OCoLC)981487118version: Vinod, Hrishikesh D., 1939- Hands-on matrix algebra using R. Singapore ; Hackensack, N.J. : World Scientific, ©2011 (OCoLC)981487118
Includes bibliographical references (pages 321-323) and index.
Keywords: Matrices; R (Computer program language)